A Modified Arthroscopic Ulnar Tunnel Technique for Combined Foveal and Capsular (All-Inside) Fixation of Triangular Fibrocartilage Complex Injury - Simonsen, Sabine; Gvozdenovic, Robert (Journal of Wrist Surgery, 2023)
Background Traumatic disruption of the triangular fibrocartilage complex (TFCC) is commonly present in various wrist traumas. A variation of surgical techniques is previously developed for different injury patterns. To our knowledge, only a few studies have investigated the fixation of combined foveal and capsular TFCC injuries using the ulnar tunnel technique.Purpose This prospective cohort study of 21 patients aimed to evaluate the clinical and patient-reported outcome at 2 years of follow-up after arthroscopic TFCC of combined, foveal, and capsular reattachment by modified ulnar tunnel technique.Methods Pain, grip strength, wrist motion, inclusive rotation, and patient-reported outcomes were assessed pre- and postoperatively at 2 years of follow-up.Results No complications occurred preoperatively. Pain and patient-reported outcomes improved significantly (p < 0.0001 and 0.004). Grip strength improved, but not significantly (p = 0.088). The range of motion remained unchanged. All the patients achieved full stability of the distal radioulnar joint. Two patients sustained a new TFCC injury due to a wrist trauma and underwent a reoperation successfully. Two patients experienced complications: one patient experienced tenderness caused by cyst occurrence after PushLock ankers and the second had subluxation of the extensor carpi ulnaris tendon subsheet. Both patients were successfully treated and reoperated on with curettage of the cyst, and reconstruction of the extensor carpi ulnaris retinaculum. All the patients ended with good or excellent satisfaction scores.Conclusion The ulnar tunnel technique for combined foveal and capsular injuries shows promising short-term follow-up results and high satisfaction scores in the patients.Level of Evidence II (Prospective Corhorte).
Keywords: TFCC; ulnar pain; triangular fibrocartilage lesion; fixation; arthroscopic suture